Tương quan của chỉ số thực vật tới cân bằng nước lưu vực sông Phó Đáy - Thạch, Nguyễn Ngọc (Vietnam Journal of Earth Sciences, 2005)
Water supplying in dry season is a very interested problem for water balancing study in a small and medium catchment area. The study concentrated to extract the NDVI values from remote sensing data such as LANDSAT-TM or SPOT and then to determine the correlation of vegetation with NDVI values to water recharge . Result of the study show that if the NDVI value of minimum 30% of the transited area in the catchment exceeded to 0.3 than the regulation capacity of vegetation would be strongly effectived. It is an index which can be stored in the data set for water balance study.